Technology-Enhanced Project-Based Learning for EFL Learners: A Narrative Review of Digital Innovation in Speaking Instruction - Rakhmanina, Lisa; Arono (Corolla International Conference, 2025)
This narrative literature review explores how Project-Based Learning (PBL) might improve EFL speaking abilities with technology. This review synthesizes twelve empirical and conceptual studies from 2019 to 2024 on how digital tools like mobile apps, video blogs, social media platforms, and audiovisual media enhance learner engagement and oral language development as PBL frameworks. Results show that technology-enhanced project-based learning improves students’ spoken fluency, confidence, and vocabulary while creating more authentic and stimulating learning settings. Digital platforms improve learning outside of the classroom, stimulate cooperation, and let students use language in meaningful ways. However, the research highlights inconsistent assessment techniques, short-term solutions, and teacher preparedness and infrastructural issues. The studies use different methods and focus on different regions, highlighting the need for longitudinal and comparative research across educational contexts. The review concludes that technology-enhanced project-based learning requires careful pedagogical preparation, resources, and educator professional development. This synthesis shows how student-centered, project-driven, communications and engagement-focused digital innovation can improve language learning.